Aulostemon (Asparagaceae, Scilloideae), a new genus from South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2017)
As part of a taxonomic revision of Hyacinthaceae subfamily Urgineoideae (Asparagaceae tribe Urgineeae) based on morphological and genetic data covering numerous samples from its whole range of distribution, we here describe a new genus from south-eastern South Africa. Aulostemon includes Drimia mzimvubuensis, a species recently placed in Sagittanthera. However, distinct morphological character states, especially regarding connation of stamen filaments to form a distinct tube that surrounds the gynoecium, the free anthers, the lack of bracteoles and its isolated phylogenetic position within subfamily Urgineoideae, support the description of the new genus.